Energy saving potential of ground integrated architecture on slope terrains - Marinho de Castro, Maria Manuela (2017)
Fast urban growth and topographical factors across Europe have contributed to an increase in the total number of hillside residential buildings. In the case of Portugal, a clear need for hillside building design which can fully benefit from the thermal advantage of slope terrains has been identified. Although the energy efficiency of ground-integrated architecture has been the subject of numerous research works, only a small number of those research projects have focused on the thermal potential of ground-integrated buildings constructed on sloped terrains. The research presented in this thesis sheds light on the energy saving potential of ground-integrated buildings on slope terrains and provides design guidelines based on the research findings. Firstly, through mathematical calculations, this research demonstrates that ground thermal patterns under slope terrains are different from those below flat areas. In Lisbon, terrain inclinations have higher annual ground thermal potential than flat terrains. It is furthermore noted that a transitional zone is formed immediately before and after a slope. As a result of these investigations it is concluded that slopes of 30° to 40° provide the best annual ground thermal potential. Secondly, through a parametric study using EnergyPlus to simulate ground heat transfer, it is show that ground integration affects buildings thermal performance. It is found that the greater the ground integration the lower the energy demand, but also that total ground integration fails to provide the best solution. Concerning the levels of slope integration, the steeper the slope, the greater the average annual savings. However the thermal advantage difference between steeper slopes such as those of between 30° to 50° is small. Regarding the impact of building design on annual saving potential, it is found that building design does affect models’ thermal performance and that its impact is greatest with shallower slopes. It is therefore concluded that in temperate climates, new hillside constructions can take advantage of the energy saving potential of ground integration into slope terrain and of slope building designs.